Blocking NMDA-receptors in the pigeon’s “prefrontal” caudal nidopallium impairs appetitive extinction learning in a sign-tracking paradigm - Lengersdorf, Daniel; Marks, David; Uengoer, Metin; Stüttgen, Maik C.; Güntürkün, Onur (Frontiers in Behavioral Neuroscience, 2015)
Extinction learning provides the ability to flexibly adapt to new contingencies by learning to inhibit previously acquired associations in a context-dependent manner. The neural networks underlying extinction learning were mostly studied in rodents using fear extinction paradigms. To uncover invariant properties of the neural basis of extinction learning, we employ pigeons as a model system. Since the prefrontal cortex of mammals is a key structure for extinction learning, we assessed the role of N-methyl-D-aspartate receptors (NMDARs) in the nidopallium caudolaterale, the avian functional equivalent of mammalian prefrontal cortex. Since NMDARs in prefrontal cortex have been shown to be relevant for extinction learning, we locally antagonized NMDARs through 2-Amino-5-phosphonovalerianacid (APV) during extinction learning in a within-subject sign-tracking ABA-renewal paradigm. APV-injection slowed down extinction learning and in addition also caused a disinhibition of responding to a continuously reinforced control stimulus.. In subsequent retrieval sessions, spontaneous recovery was increased while ABA renewal was unaffected. The effect of APV resembles that observed in studies of fear extinction with rodents, suggesting common neural substrates of extinction under both appetitive and aversive conditions and highlighting the similarity of mammalian prefrontal cortex and the avian caudal nidopallium despite 300 million years of independent evolution.